Seashells of southern Florida : living marine mollusks of the Florida keys and adjacent regions, bivalves - Mikkelsen, Paula M. (Princeton University Press, 2008)
Located where the Atlantic Ocean, Gulf of Mexico, and Caribbean Sea converge, the Florida Keys are distinctive for their rich and varied marine fauna. The Keys are home to nearly sixty taxonomic families of bivalves such as clams and mussels--roughly half the world's bivalve family diversity. The first in a series of three volumes on the molluscan fauna of the Keys and adjacent regions, Seashells of Southern Florida: Bivalves provides a comprehensive treatment of these bivalves, and also serves as a comparative anatomical guide to bivalve diversity worldwide. Paula Mikkelsen and Rüdiger Bieler cover more than three hundred species of bivalves, including clams, scallops, oysters, mussels, shipworms, jewel boxes, tellins, and many lesser-known groups. For each family they select an exemplar species and illustrate its shell and anatomical features in detail. They describe habitat and other relevant information, and accompany each species account with high-resolution shell photographs of other family members. Text and images combine to present species--to family-level characteristics in a complete way never before seen. The book includes fifteen hundred mostly color photographs and images of shells, underwater habitats, bivalves in situ, original anatomical and hinge drawings, scanning electron micrographs, and unique transparent--shell illustrations with major organ systems color-coded and clearly shown. Seashells of Southern Florida: Bivalves is the most complete guide to subtropical bivalves available. It is an essential tool for students and teachers of molluscan diversity and systematics, and an indispensable identification guide for collectors, scuba divers, naturalists, environmental consultants, and natural-resource managers.